Numerical investigation of force transmission in granular media using discrete element method - Nguyen, Thong Chung; Le, Lu Minh; Ly, Hai-Bang; Le, Tien-Thinh (Vietnam Journal of Mechanics, 2020)
In this paper, a numerical Discrete Element Method (DEM) model was calibrated to investigate the transmission of force in granular media. To this aim, DEM simulation was performed for reproducing the behavior of a given granular material under uniform compression. The DEM model was validated by comparing the obtained shear stress/normal stress ratio with results published in the available literature. The network of contact forces was then computed, showing the arrangement of the material microstructure under applied loading. The number and distribution of the contacts force were also examined statistically, showing that the macroscopic behavior of the granular medium highly depended on the force chain network. The DEM model could be useful in exploring the mechanical response of granular materials under different loadings and boundary conditions.